A Study on Reducing Heat Gains through the use of Bio-Climatic Facades - Kambil, Jidesh Padmanabhan (2009)
For centuries, humans have built shelters that were bio-climatic and adapted to the region they belonged to. They achieved comfort within their enclosures without the over-dependence on electricity. But since the advent of curtain walls and centralized air-conditioning, we have leaned towards aesthetics at the cost of performance. Pampered by the controlled internal environment, we started to live in isolation from nature, our whole existence became governed by machines and in time our lives have became an extension of the environment we now inhabit. We have also paid the price for our choices. Today the very existence of all life on earth lies on a fragile lifeline of hope. We have used our resources beyond the limit and have poisoned every sphere of life on the planet. It is not certain if there is a way back, but we are left with no more choices, we have only one option. We need to change, now. Buildings have been the surprise villains in the Carbon footprint story and we now know that much of the energy generated by man on earth goes into operating our buildings and its life supporting systems (HVAC). Today, most buildings cannot sustain life within it in the absence of energy to power the ventilation systems. By using sealed facades, we are cutting ourselves entirely from the surrounding environment. But this becomes an even bigger problem when one considers the generous use of glazing in urban architecture especially in some parts of the world like Dubai that are too hot and too bright for such architectural adventures. The overuse of glazing also brings in excess glare and heat, which is often not anticipated or understood when the designer wills a gleaming glazed tower in the middle of a dessert. What then are the solutions if any? Are there any Bio-climatic Solutions to the designer’s dilemma? In this research, the use of ETFE foil cushions as an external surface in a modular double skin façade system is explored. The material offers promising performance figures and could be a sustainable material on many fronts when compared to glass. But first it has to be tested to see whether it can help in reducing heat gains through the façade, which is often the weak point in a building’s defense against the external forces. Simulation models are used to test the performance of ETFE skin with the help of ECOTECT5.5. Heating and Cooling load values will be compared for both glass and ETFE to analyze the effectiveness of both with regard to reducing heat gains. A present worth calculation for ETFE will also be carried out to assess the economic implications of using the material in place of the more conventional glazing.